An Indian Portia : selected writings of Cornelia Sorabji, 1866 to 1954 - Sorabji, Cornelia (Zubaan, 2011)
The first woman to practice law in India and Britain, Cornelia Sorabji founded the League for Infant Welfare, Maternity and District Nursing and helped hundreds of Indian women and children during her career as one of the country's most prominent social reformers. Providing an unprecedented portrait of her influential life and work, this collection includes published writing as well as letters and diary entries gathered from private sources and the Cornelia Sorabji archives in the British Library. These documents include writings on Gandhi, the independence movement, social reform, education, welfare, the caste system and untouchability, and the position of women; they also include correspondence with figures including Judge Harrison Falkner Blair, Elena Rathbone (later Lady Richmond), the viceroys of India, and Princess Louise of England. Forewords by Brenda Hale, a justice of the Supreme Court of the United Kingdom, and Coomi Kapoor, a former president of the Indian Press Corps, illuminate the heritage that Sorabji's career and writings have left to the people of India. An essential compendium for anyone interested in-or inspired by-Sorabji, this volume reveals the depths of an extraordinary figure's dedication to public service.